2018
DOI: 10.1038/s41598-018-31740-8
|View full text |Cite
|
Sign up to set email alerts
|

Candidate protein markers for radiation biodosimetry in the hematopoietically humanized mouse model

Abstract: After a radiological incident, there is an urgent need for fast and reliable bioassays to identify radiation-exposed individuals within the first week post exposure. This study aimed to identify candidate radiation-responsive protein biomarkers in human lymphocytes in vivo using humanized NOD scid gamma (Hu-NSG) mouse model. Three days after X-irradiation (0–2 Gy, 88 cGy/min), human CD45+ lymphocytes were collected from the Hu-NSG mouse spleen and quantitative changes in the proteome of the human lymphocytes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 48 publications
1
38
0
2
Order By: Relevance
“…Previously, we used Hu-NSG mice as an alternative model to validate human radiation biodosimetry standards and used the human hematopoietic system to investigate candidate protein marker expression in vivo after radiation exposure 8,34 . In the present study, we engrafted NSG mice with human fetal CD34+ stem cells to enrich the number of human cells in the mouse blood 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we used Hu-NSG mice as an alternative model to validate human radiation biodosimetry standards and used the human hematopoietic system to investigate candidate protein marker expression in vivo after radiation exposure 8,34 . In the present study, we engrafted NSG mice with human fetal CD34+ stem cells to enrich the number of human cells in the mouse blood 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The results show that although human cell engraftment levels were similar to our earlier study 8 , the NSG mice engrafted with human fetal cells showed a larger percentage of surviving human leukocytes; approximately 50% as opposed to 25% using the human cord blood stem cell model measured 3 days after 1 Gy X-ray exposure. This allowed for the use of CD45+ cells from the peripheral blood of the Hu-NSG mice mouse as opposed to the mouse spleen in previous study 8 . Table 1 and Supplementary Figure S1 show the performance of the highest-ranking protein panel to estimate delivered dose in human peripheral blood leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Equal numbers of female and male mice were used to study gender differences. Prior to irradiation, mice (8)(9)(10) week-old males, [10][11][12] week-old females) were randomized into groups for an average body weight of 29 ± 1 g. Mice were anesthetized using an intraperitoneal injection a mixture of ketamine and xylazine (80 mg/kg ketamine and 4 mg/kg xylazine) and an ophthalmic ointment was applied to prevent corneal drying (Puralube 1 vet ointment, Dechra Veterinary Products, Northwich, UK). Anesthetized mice were placed in a jig (S1 Fig) with the thorax positioned so that a 2.75 cm wide strip was exposed to X-rays administered vertically with a focus-to-surface distance of 32 cm with the rest of the body shielded with 3 mm lead that gives 99.5% attenuation.…”
Section: Whole Thorax Lung Irradiation (Wtli)mentioning
confidence: 99%
“…Biomarkers to predict both acute and late adverse outcomes of radiation exposure are critically needed to identify individuals at risk after a radiological incident, especially since early therapeutic intervention can dramatically improve survival rates in the context of ARS [1][2][3][4][5][6], and perhaps late disease [2]. Efforts into monitoring changes in blood or plasma have yielded encouraging data and identified potential biomarkers of radiation exposure, including proteins [7][8][9][10], mRNA [11][12][13][14][15][16], non-coding RNA [17], and microRNA (miRNA) [18][19][20][21][22][23][24]. Because circulating miRNA are protected from degradation in extracellular vesicles or protein complexes, and are stable at room temperature for hours to days, they are exceptionally well suited for triage in the field [25].…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has been validated through several NATO and RENEB exercises (16,18,19). A single gene expression analysis [e.g., ferredoxin reductase, (FDXR), also reported to be a protein biomarker of radiation exposure, (20)] can offer accurate information on dose received in vivo in humans across a large range of doses from CT scan to total-body exposure (14). However, a radiation signature can provide further information about homogeneity of exposure (21), mixed exposure (22) or dose rate (11).…”
Section: Introductionmentioning
confidence: 99%